2020
DOI: 10.18203/2349-3291.ijcp20200100
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of congenital cyanotic heart disease in neonatal period: a retrospective study

Abstract: Background: Congenital Cyanotic Heart Disease (CCHD) is under reported during neonatal period and mortality rate is high in India. Aims and objectives of the study determine clinical presentation, maternal and neonatal risk factors and outcome of CCHD during neonatal period.Methods: A retrospective study conducted over 15-month period during March 2017 to June 2018 in a tertiary out born NICU. Neonates with echocardiographically confirmed case of structurally abnormal heart disease were analyzed.Results: Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…Increasing cyanosis was the most common presenting symptom followed by fever and respiratory distress, which aligns with findings reported by Al-Hamash [12] and Pradhan et al [13]. Respiratory distress and fever are common presenting symptoms in studies that include cyanotic and acyanotic CHDs [14].…”
Section: Discussionsupporting
confidence: 87%
“…Increasing cyanosis was the most common presenting symptom followed by fever and respiratory distress, which aligns with findings reported by Al-Hamash [12] and Pradhan et al [13]. Respiratory distress and fever are common presenting symptoms in studies that include cyanotic and acyanotic CHDs [14].…”
Section: Discussionsupporting
confidence: 87%
“…17 TGA was the most common CCHD in neonatal period (27.9%) in a study conducted in Srinagar. 18 In another study conducted in Chennai 19 , TGA was the most common CCHD noted in 33.9% of cyanotic congenital heart disease neonates. Similarly a study by Lynch A et al 20 showed that TGA was the most common cyanotic CHD in prenatal as well as post natal period.…”
Section: Resultsmentioning
confidence: 97%
“…17 In a study carried out in Tamil Nadu, pulmonary atresia was the second most common cyanotic CHD after TGA. 19 In another study done in Aga Khan University Hospital 16 , TOF with its variants was the most common CHD as pulmonary atresia was not considered as a separate entity. Pulmonary atresia is the third commonest cyanotic congenital defect with a frequency of 18.4% in our study.…”
Section: Resultsmentioning
confidence: 99%